Agrobiodiversity for People and Planet: How Multifunctional Landscapes Safeguard Diversity, Resilience, and Livelihoods - Edward-Uwadiale, Regina; Kettle, Chris; Fadda, Carlo; Masso, Cargele (CGIAR System Organization, 2025)
The article highlights how agrobiodiversity-rich, multifunctional landscapes can transform agricultural systems to support both people and the planet. Rather than degrading nature, diversified farming systems that integrate crops, trees, livestock, and aquatic foods enhance biodiversity, improve resilience to climate shocks, and support nutritious diets and rural livelihoods. These nature-positive approaches align with global biodiversity goals such as the Kunming–Montreal Global Biodiversity Framework and demonstrate practical pathways for sustainable food production. Examples from diverse regions show how integrating biodiversity into landscapes boosts productivity, sustains ecosystem services, and advances policy and investment frameworks necessary to scale these solutions. Ultimately, multifunctional landscapes offer a practical strategy to meet food security and conservation objectives together.